A BE-based Multi-document Summarizer with Query Interpretation - Zhou, Liang; Lin, Chin-Yew; Hovy, Eduard (2005)
This paper describes the multi-document summarization system designed by the Webclopedia team from ISI for DUC 2005. In contrast to the past DUCs and previous designs, this version of our summarizer consists of a query-interpretation component that directly analyzes the given user profile and topic narrative for each document cluster before creating a corresponding summary. This system ranks 4th on ROUGE-1, 7th on ROUGE-2 and ROUGE-SU4. Evaluations conducted by Basis Elements show this system ranks 6th among 32 automatic systems.